Entry conditions and the transition from tertiary education to employment - John D. Moffat; Duncan Roth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
This paper uses monthly data on tertiary education graduates in 17 European countries covering 2004-2017 to assess the short-run effects of entry conditions on the transition into employment. Using an instrumental variables approach, an increase in the graduation unemployment rate of one percentage point is found to reduce the hazard rate of transitioning from unemployment into employment by 3.6 percent. This effect is stronger for females than males although the difference disappears when analysing transitions from inactivity into employment. A longer duration of initial unemployment may therefore help to explain long-run negative effects of unfavourable entry conditions found in earlier studies. – – Anhand von Daten zu Hochschulabsolventinnen und -absolventen aus 17 europäischen Ländern und den Jahren 2004-2017 untersuchen wir die kurzfristigen Auswirkungen, die die Bedingungen zum Zeitpunkt des Eintritts in den Arbeitsmarkt auf den Übergang in Beschäftigung haben. Mit einem Instrumentvariablenansatz schätzen wir, dass ein Anstieg in der Arbeitslosenquote zum Zeitpunkt des Abschlusses um einen Prozentpunkt die Hazardrate eines erfolgreichen Übergangs in Beschäftigung um 3,6 Prozent reduziert. Dieser Effekt fällt für Frauen stärker aus als für Männer. Berücksichtigt man jedoch Übergänge aus Inaktivität in Beschäftigung, stellt sich dieser Unterschied nicht ein. Eine längere Arbeitslosigkeit nach Eintritt in den Arbeitsmarkt könnte einen Grund für die aus anderen Studien bekannten langfristigen folgen ungünstiger Eintrittsbedingungen darstellen.
Keywords: J64; J11; J23; 330; Cox proportional hazards model; entry conditions; graduates; residual inclusion; transition to employment